Ixora Chinensis Lamk: A Flower Extract Health Drink - Srichaikul, Buavaroon (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2016)
Health Drinks currently are one of the most popular demand of consumptiondrink product in Thailand globally . We found that many anti-aging health drink productswere developed under sub- standard and did not meet the Thai FDA requirements in the areaof toxicities and bioactivities. This study aimed to evaluate the anti oxidant activities ofdifferent methods of extraction and maceration of solvents , bioactivity quantities , toxicity,active ingredients of Ixora chinensis Lamk., flower extract health drink .